New Technology Adoption Framework for Telecom Operators - with focus on Block chain (International Journal of Scientific Research and Management (IJSRM), 2017)
Adopting new technology in existing business is one of the toughest decisions that CXO’s needto take. Till a technology becomes main stream, there are no clear strategies that can be used to defineadoption roadmaps. Blockchain poses such a problem for senior executives as it is one of the mostpromising disruptive technologies, but is still in its infancy. To help decision makers, this paper proposesa new technology adoption framework. The adoption framework will help Executives create testing andadoption strategies for new technologies. To clearly explain framework, an adoption scenario forTelecom operator wanting to use block chains has also been documented